Applied statistical modeling - Babones, Salvatore (Los Angeles : SAGE, 2013)
This new four-volume set brings together seminal articles in the field, selected for their exemplification of the specific model type used, their clarity of exposition and their importance to the development of their respective disciplines.
Includes bibliographical references.
Keywords: Social sciences -- Statistical methods; Social sciences -- Mathematical models